A modified Duvaut-Lions zero-thickness interface model for simulating the rate-dependent bond behavior of FRP-concrete joints - Caggiano, Antonio (2018)
This paper proposes a model aimed at simulating the strain-rate effect in Fiber Reinforced Polymer (FRP) strips glued to concrete. More specifically, the loading rate-dependent bond mechanisms are evaluated by extending a classical overstress viscoplastic approach, available in the literature, generally referred to as Duvaut-Lions’ approach. The model is formulated within the general theoretical framework of fracture mechanics under the assumption that debonding occurs as a pure mode II cracking process. Zero-thickness interface elements were employed for implementing the aforementioned FRP-to-concrete joint model. From the conceptual viewpoint, the model is used in an incremental analysis and the debonding phenomenon is simulated as a propagating fracture whose local residual stress is described by the decreasing branch of a bond-slip law assumed “a priori”. The mechanical soundness of the proposed model is demonstrated by the very good agreement between some experimental results, taken from the scientific literature, and the corresponding numerical predictions at significantly diverse loading rates ranging from 0.07 to 70 mm/s.